Examination and the State of Intoxication: Features of Legal Regulation and Observance of Human Rights and Freedoms (Law and Safety, 2020)
The author of the article examines the state of alcohol, drugs or other intoxication, as well as the influence of drugs that reduce the attention and speed of reaction, as a measure to ensure the proceedings in cases of administrative offenses, and features of legal regulation of its use during documentation of administrative offenses, as well as the admissibility of using the obtained data as evidence in proceedings on administrative offenses.The examination of the state of intoxication is not just a measure to ensure the proceedings in cases of administrative offenses, but a necessary procedural action, which allows to assert the presence in the actions of a person of an administrative offense.It is alleged that an examination of the state of intoxication, in particular of drivers, is possible only if they are detained administratively. It is applied to the documentation of other administrative offenses, the proof of which requires the establishment of a state of intoxication. In other circumstances, such an examination of intoxication should be considered inadmissible evidence in an administrative offense case, since it was obtained in substantial violation of human rights and freedoms, including the right to liberty and security, as well as a number of other rights, which the detained person failed to exercise.It is appropriate that such a security measure as the removal of a driver from driving the vehicle had a procedural form, in this regard, we consider it necessary to supplement the Art. 266 of the Code of Administrative Offenses with Part 8 of the following wording: «On the removal of persons from driving vehicles, river and small vessels authorized officials execute the minutes».We are confident that the offered amendments to the legislation will contribute to the development of administrative tort law, its institutions, which positively affect both the legal system and legislation of independent Ukraine, raising the prestige of its legal system in the world, and serve as a convincing argument for citizens to become victims of arbitrariness of authorities.
Keywords: enforcement measures; an administrative offense; review of intoxication; human rights and freedoms